2022
DOI: 10.3390/foods11162463
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Specific Activity and Thermostability of Psychrophilic Xylosidase AX543 by Comparative Mutagenesis

Abstract: Improving the specific activity and thermostability of psychrophilic xylosidase is important for improving its enzymatic performance and promoting its industrial application. Herein, a psychrophilic xylosidase AX543 exhibited activity in the temperature range between 0 and 35 °C, with optimum activity at 20 °C, which is lower than that of other reported psychrophilic xylosidases. The thermostability, specific activity, and catalytic efficiency of the site-directed variants G110S, Q201R, and L2 were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Numerous publications have demonstrated that xylanase characteristics from the GH10 and GH11 families can be improved using protein engineering methods, and few publications have explored improving the catalytic performance of enzymes from the GH43 family using site-directed mutagenesis (10,20). In this work, protein engineering methods were used to improve the catalytic performance of Xyn ZT-2 based on evolutionary analysis.…”
Section: Selection Of Mutation Sites Based On Evolution Analysismentioning
confidence: 99%
“…Numerous publications have demonstrated that xylanase characteristics from the GH10 and GH11 families can be improved using protein engineering methods, and few publications have explored improving the catalytic performance of enzymes from the GH43 family using site-directed mutagenesis (10,20). In this work, protein engineering methods were used to improve the catalytic performance of Xyn ZT-2 based on evolutionary analysis.…”
Section: Selection Of Mutation Sites Based On Evolution Analysismentioning
confidence: 99%
“…JB13 showed a relative activity of 20% at 20 °C owing to the high flexibility resulting from its high frequency of small amino acids and high proportion of random coils . Conversely, the increased rigidity of structure could improve the thermostability of enzyme . Some Loops are critical for the structural rigidity of the enzyme .…”
Section: Biochemical Properties Of β-Xylosidasesmentioning
confidence: 99%
“…45 Conversely, the increased rigidity of structure could improve the thermostability of enzyme. 97 Some Loops are critical for the structural rigidity of the enzyme. 98 Moreover, an oligomeric state, relatively longer asparagine ladder, and glycosylated amino acids can enhance the thermostability of enzymes.…”
Section: Temperature Properties Of β-Xylosidasesmentioning
confidence: 99%